İlaç fiyatlandırma ve geri ödeme politikalarının orijinal ilaç ve jenerik ilaç açısından değerlendirilmesi: Hipertansiyon ilaçları örneği - Kumru, Seda; Top, Mehmet (My University, 2017)
İlaç fiyatlandırma ve geri ödeme politikaları ilaca erişimi, maddi karşılanabilirliği ve akılcı kullanımı hedefler. Bu çalışmanın amacı ilaç fiyatlandırma ve geri ödeme politikalarını orijinal ve jenerik ilaçlar açısından değerlendirmektir. Çalışmada, ilaç fiyatlandırma ve geri ödeme politikaları 2007-2012 yıllarında hipertansiyon ilaçlarının fiyat, tüketim ve harcama verileri kullanılarak değerlendirilmiştir. Bu çalışma fiyat kesintileri gibi doğrudan müdahalelerin Türkiye’de ilaç fiyatlandırma ve geri ödeme sisteminde baskın olduğunu göstermiştir. 2007-2012 yılları arasında ilaç fiyatlandırma politikaları jenerik ilaç fiyatlarını önemli derecede düşürürken, zorunlu kamu indirimleri gibi geri ödeme politikaları orijinal ilaçların fiyatlarını büyük ölçüde azaltmıştır. Türkiye’de, ilaç fiyatlandırma ve geri ödeme politikalarının akılcı ilaç kullanımı, jenerik ilaç kullanımının desteklenmesi ve jenerik ikame gibi talebe yönelik müdahalelere odaklanması gerektiği düşünülmektedir.

Pharmaceutical pricing and reimbursement policies aim to ensure the availability, affordability and rational use of medicines. The aim of this study is to evaluate drug pricing and reimbursement policies with regard to orijinal drug and generic drug. In this study, effects of drug pricing and reimbursement policies related to original drug and generic drugs are evaluated by using of price, consumption and expenditure data of hypertension drugs between the 2007-2012 years. This study showed that direct interventions such as price cut are predominant for drug pricing and reimbursement system in Turkey. Between the 2007- 2012 years, while drug pricing policies have substantially reduced generic drugs price, and also drug reimbursement policies, such as compulsory public discount, considerably decreased original drug price. In Turkey, it is thought that drug pricing and reimbursement policies are needed to focus on interventions to demand such as rational use of drug, encouraging the use of generic medicines, generic substitution.
Evaluation of pharmaceutical pricing and reimbursement policies with regard to original drug and generic drug: A case of hypertension drugs
Keywords: İlaç Fiyatlandırma ve Geri Ödeme Politikaları; Orijinal İlaçlar; Jenerik İlaçlar; Drug Pricing and Reimbursement Policies; Original Drugs; Generic Drugs